Observation of Λb0 → ψ(2S)pK− and Λb0→ J/ψ π+ π− pK- decays and a measurement of the Λb0 baryon mass - Cheung, S; Evans, T; Gandini, P; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; Topp-Joergenson, S; et al. (Springer, 2016)
The decays Λb0→ ψ(2S)pK− and Λb0→ J/ψπ+π−pK−are observed in a data sample corresponding to an integrated luminosity of 3 fb^−1, collected in proton-proton collisions at 7 and 8 TeV centre-of-mass energies by the LHCb detector. The ψ(2S) mesons are reconstructed through the decay modes ψ(2S) → μ+μ−and ψ(2S) → J/ψπ+π−. The branching fractions relative to that of Λb0→ J/ψpK−are measured to be ℬ(Λb0→ψ(2S)pK−)/ℬ(Λb0→J/ψpK−) = (20.70±0.76±0.46±0.37) × 10^−2, ℬ(Λb0→ψ(2S)pK−)/ℬ(Λb0→J/ψpK−) = (20.86±0.96±1.34)×10^−2 where the first uncertainties are statistical, the second are systematic and the third is related to the knowledge of J/ψ and ψ(2S) branching fractions. The mass of the Λb0baryon is measured to be M(Λb0) = 5619.65 ± 0.17 ± 0.17MeV/c2, where the uncertainties are statistical and systematic.